2022
DOI: 10.33094/ijaefa.v13i2.617
|View full text |Cite
|
Sign up to set email alerts
|

Risk Monitoring Committee and Firm Value of Listed Oil and Gas Companies in Nigeria: A Panel Data Analysis

Abstract: In this paper, the relationship between the risk monitoring committee (RMC) and the firm value of listed Nigerian oil and gas firms was examined. The risk monitoring committee was measured via the presence and size of the risk committee and the contributions of non-executive directors, while firm value was measured using Tobin’s Q, price-to-earnings per share, and earnings yield. Data were collected from the Machamratios database for the period 2012–2020. An aggregate panel data of eight (8) firms was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A group of studies have used legitimacy theory to examine disclosure practices green and social among companies (Deegan, 2013;Michelon et al, 2015;Pitrakkos and Maroun, 2020;Agbarha, 2022;Ahmad et al, 2022;Alnaa and Matey, 2022). It was emphasized that the support from the community was very much important for sustainability, survival, growth and corporate image.…”
Section: Theories Related To Green Accountingmentioning
confidence: 99%
“…A group of studies have used legitimacy theory to examine disclosure practices green and social among companies (Deegan, 2013;Michelon et al, 2015;Pitrakkos and Maroun, 2020;Agbarha, 2022;Ahmad et al, 2022;Alnaa and Matey, 2022). It was emphasized that the support from the community was very much important for sustainability, survival, growth and corporate image.…”
Section: Theories Related To Green Accountingmentioning
confidence: 99%
“…Alternative energies have been widely studied in the literature as a means of improving environmental performance and mitigating the impacts of climate change. Researchers have consistently found that the increased usage of alternative energies can help to reduce CO 2 emissions (Adebayo and Kirikkaleli, 2021;Ayobamiji et al, 2022;Bamisile et al, 2021;Bekun, 2022;Charfeddine and Kahia, 2019;Ehigiamusoe and Dogan, 2022;Gielen et al, 2019;Haldar and Sethi, 2022;Qin et al, 2021;Hao et al, 2021;Hasnisah et al, 2019;Wang et al, 2020;Pata and Caglar, 2021;Sahoo and Sahoo, 2022;Sharif et al, 2020;Vo et al, 2020;Ali et al, 2021;Yuan et al, 2022;Zafar et al, 2019;Agbarha, 2022;Ahmad et al, 2022;Alnaa and Matey, 2022;Belesis et al, 2022;Faisal et al, 2022;Imasuen et al, 2022). Hao et al (2021), for example, found that the increased use of alternative energy sources can help to reduce emissions, which adds to air pollution and negative impacts on human health.…”
Section: Literature Reviewmentioning
confidence: 99%